Short-term storage of the oocytes affects the ploidy status in the yellowtail tetra Astyanax altiparanae - Santos, Matheus Pereira dos [UNESP]; Nascimento, Nivaldo Ferreira do [UNESP]; Yasui, George Shigueki; Pereira, Nycolas Levy [UNESP]; Fujimoto, Takafumi; Senhorini, Jose Augusto; Okada Nakaghi, Laura Satiko [UNESP] (Cambridge Univ Press, 2018)
In fish, many factors can affect reproduction during in vitro fertilization, therefore determination of the factors that affect affecting gamete quality is needed. However, few studies have focused on gamete quality and the ploidy status. This study was conducted to elucidate whether oocyte storage can affect ploidy status, survival, and embryo viability in the characid species Astyanax altiparanae. Oocytes were stored in Dulbecco's phosphate-buffered saline (PBS) at 26 degrees C, then aliquots were fertilized immediately after extrusion (control) and also after 60, 120, 180, and 240 min of storage. Fertilization and hatching rates were measured, and the developmental stages were analyzed at each stage before describing the main abnormalities. Ploidy status was analyzed by flow cytometry and blood smear. In the control group, 100% of the samples were diploid. After treatment for 60 min, 95.56 +/- 4.44% samples were diploid and 4.44 +/- 4.44% were triploid. After 120 min, 94.44 +/- 9.62% of the samples was diploid and 5.56 +/- 5.56% were triploid; 100% of the samples were diploid after 180 min and, after 240 min, there was no survival. In other treatments, the highest percentage of hatching was after 60 min (88.93 +/- 5.15%; P = 0.015), and treatment with 180 min storage resulted in the highest percentage of abnormal larvae (95.76 +/- 12.67%; P = 0.012). These results show that oocyte storage can affect ploidy status and may be an interesting parameter for analysis in studies on chromosome set manipulation and micromanipulation.
Keywords: Embryogenesis; Gametes; Morphology; Polyploidy; Reproduction